Time-dependent photoemission from droplets: influence of size and charge on the photophysics near the surface. (4th May 2022) - Ban, Loren; Tang, Hanchao; Yoder, Bruce L.; Signorell, Ruth
Abstract : Time-resolved photoemission spectroscopy is used to study the photophysics of droplets containing dioctyl phthalate. Long-lived excited states survive longer at lower phthalate concentrations, and in larger or electrically charged droplets. Abstract : Photoemission from submicrometer droplets containing a mixture of dioctyl phthalate and dioctyl sebacate was investigated by femtosecond and nanosecond photoionization. Photoelectron spectra recorded after ionization with single 4.7 eV femtosecond or nanosecond laser pulses showed marked differences between the two cases. These differences were attributed to ionization of long-lived states which only occurred within the duration of the nanosecond pulse. The tentative assignment of the long-lived states to dioctyl phthalate triplet states is discussed. A nanosecond–femtosecond pump–probe scheme using 4.7 eV (pump) and 3.1 eV (probe) pulses was used to investigate the decay dynamics of these long-lived states. The dynamics showed an accelerated decay rate at higher dioctyl phthalate concentrations. Furthermore, the dependence of the decay dynamics on droplet size and charge was investigated. The decay of the long-lived states was found to be faster in smaller droplets as well as in neutral droplets compared with both positively and negatively charged droplets. Possible mechanisms to explain these observations and the dominance of contributions from the droplets surface are discussed.